Crosstalk between septic shock and venous thromboembolism: a bioinformatics and immunoassay analysis - Li, Zhishu; Wang, Chaolan; Zhang, Xu; Xu, Xiaolin; Wang, Meng; Dong, Lixia (Frontiers in Cellular and Infection Microbiology, 2023)
Background Herein, we applied bioinformatics methods to analyze the crosstalk between septic shock (SS) and venous thromboembolism (VTE), focusing on the correlation with immune infiltrating cells. Methods Expression data were obtained from the Gene Expression Omnibus (GEO) database, including blood samples from SS patients (datasets GSE64457, GSE95233, and GSE57065) and VTE patients (GSE19151). We used the R package "limma" for differential expression analysis (p value<0.05,∣logFC∣≥1). Venn plots were generated to identify intersected differential genes between SS and VTE and conducted Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) Enrichment analysis. The protein-protein interaction (PPI) network of intersected genes was constructed by Cytoscape software. The xCell analysis identified immune cells with significant changes in VTE and SS and correlated them with significant molecular pathways of crosstalk. Finally, we validated the mRNA expression of crosstalk genes by qPCR, while Matrix Metalloprotein-9 (MMP-9) protein levels were assessed through Western blotting (WB) and Immunohistochemistry (IHC) in human umbilical vein endothelial cells (HUVECs) and mice. Results In the present study, we conducted a comparison between 88 patients with septic shock and 55 control subjects. Additionally, we compared 70 patients with venous thromboembolism to 63 control subjects. Twelve intersected genes and their corresponding three important molecular pathways were obtained: Metabolic, Estrogen, and FOXO signaling pathways. The resulting PPI network has 194 nodes and 388 edges. The immune microenvironment analysis of the two diseases showed that the infiltration levels of M2 macrophages and Class-switched memory B cells were correlated with the enrichment scores of metabolic, estrogen, and FOXO signaling pathways. Finally, qPCR confirmed that the expression of MMP9, S100A12, ARG1, SLPI, and ANXA3 mRNA in the SS with VTE group was significantly elevated. WB and IHC experiments revealed that MMP9 protein was significantly elevated in the experimental group. Conclusion Metabolic, estrogen, and FOXO pathways play important roles in both SS and VTE and are related to the immune cell microenvironment of M2 macrophages and Class-switched memory B cells. MMP9 shows promise as a biomarker for diagnosing sepsis with venous thrombosis and a potential molecular target for treating this patient population.